Topological Structure of the Solution Set of a Cauchy Problem for Fractional Differential Inclusions with an Upper Semicontinuous Right-Hand Side - Petrosyan, G. G. (Doklady. Mathematics, 2025)
We study the topological structure of the solution set of the Cauchy problem for semilinear differential inclusions of fractional order in Banach spaces. It is assumed that the linear part of the inclusions is a linear closed operator generating a strongly continuous and uniformly bounded family of cosine operator functions. The nonlinear part is represented by an upper semicontinuous multivalued operator of Carathéodory type. It is established that the solution set of the problem is an -set.